UNPACKING THE EVALUATION–PERFORMANCE LINK: THE ROLE OF SUBORDINATE TRUST IN SUPERVISORS - Desriani, Neny (Faculty of Economics and Business, 2025)
This study unpacks the relationship between formal performance evaluation and job performance by examining the mediating role of subordinates’ trust in their supervisors. Data were collected through an online survey of 103 teachers from private schools in Indonesia and analyzed using Structural Equation Modelling (SEM) with Smart PLS 4.0. The findings reveal that formal performance evaluation systems foster greater trust in supervisors, which in turn significantly enhances job performance. Theoretically, this study extends the performance evaluation literature by highlighting trust as a critical relational mechanism that connects evaluation practices to employee outcomes. Practically, the results emphasize the strategic importance of cultivating trust through fair and structured evaluation systems to improve organizational effectiveness.